2007
DOI: 10.1007/s00262-007-0416-y
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with metastasis-related tumor associated antigen TPD52 and CpG/ODN induces protective tumor immunity

Abstract: Tumor protein D52 (TPD52) is involved in transformation and metastasis and has been shown to be over-expressed in tumor cells compared to normal cells and tissues. Murine TPD52 (mD52) shares 86% protein identity with the human TPD52 orthologue (hD52). To study TPD52 protein as a target for active vaccination recombinant, mD52 was administered as a protein-based vaccine. Naïve mice were immunized with either mD52 protein and CpG/ODN as a molecular adjuvant or CpG/ODN alone. Two weeks following the final immuniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 38 publications
2
35
0
Order By: Relevance
“…S1), a protein frequently overexpressed in breast and other cancers (31) and a potential tumor antigen target for immunotherapy (32)(33)(34), D-3-phosphoglycerate dehydrogenase (PHGDH) (IEF SSP#2512; NEPHGE SSP# 2601, Supplemental Figs. S1 and S2, respectively), a protein involved in the serine biosynthetic pathway that was recently identified in ER-negative breast cancer (35,36), and melanoma-associated antigen 4 (Mage-A4) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S1), a protein frequently overexpressed in breast and other cancers (31) and a potential tumor antigen target for immunotherapy (32)(33)(34), D-3-phosphoglycerate dehydrogenase (PHGDH) (IEF SSP#2512; NEPHGE SSP# 2601, Supplemental Figs. S1 and S2, respectively), a protein involved in the serine biosynthetic pathway that was recently identified in ER-negative breast cancer (35,36), and melanoma-associated antigen 4 (Mage-A4) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…99 When mD52 DNA vaccination was compared head-to-head with hD52 DNA vaccination, the partial xeno-antigen (hD52) was more effective at protecting against tumor challenge, however both strategies induced durable responses that rejected secondary tumor challenge months later. 100 The T cell cytokine secretion patterns for all the TPD52 vaccine studies demonstrated that a T H -1-type cellular immune response was responsible for tumor rejection [97][98][99] and that a complete response may be hindered by a potentially unique subset of CD8C IL-10C regulatory T cells. 100 An overlapping peptide-based mD52 vaccine, evaluated independently, demonstrated efficacy in a murine breast cancer model.…”
Section: Tpd52 As a Vaccine Targetmentioning
confidence: 99%
“…First, the successful use of the basic vaccine formulation demonstrated that a tumor self-protein can be immunogenic when delivered as a simple protein, peptides or plasmid DNA. Second, TPD52 vaccines prevent tumor formation without inducing autoimmunity, 97 even when classical CD4C CD25C Treg cells were depleted. 98,100 These studies suggest that TPD52-specific T cells are present and not completely eliminated by central tolerance, and that peripheral tolerance is involved in obstructing complete tumor rejection to include suppression by an as yet undefined but potentially unique subset of CD8C Treg cells.…”
Section: Tpd52 As a Vaccine Targetmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, D52 represents a non-mutated over-expressed self-oncoantigen. We demonstrated for the first time that mD52 induces protection against tumor challenge when administered as recombinant protein-based vaccine with CpG-ODN [13]. We also reported that mD52 DNA vaccination induced an immune response that rejected tumors in the transgenic adenocarcinoma of the mouse prostate (TRAMP) model of prostate cancer.…”
Section: Introductionmentioning
confidence: 76%